Purification and Characterization of Nk‐3FTx: A Three Finger Toxin from the Venom of North East Indian Monocled Cobra. Issue 2 (21st August 2015) - Das, Diganta; Sharma, Maitreyee; Kumar Das, Hemanga; Pratim Sahu, Partha; Doley, Robin
ABSTRACT: Snake venom three finger toxins (3FTxs) are a non‐enzymatic family of venom proteins abundantly found in elapids. We have purified a 7579.5 ± 0.591 Da 3FTx named as Nk‐3FTx from the venom of Naja kaouthia of North East India origin. The primary structure was determined by a combination of N‐terminal sequencing and electrospray ionization  liquid chromatography‐mass spectrometry/mass spectrometry. Biochemical and biological characterization reveal that it is nontoxic to human cell lines and exhibit mild anticoagulant activity when tested on citrated human plasma. Nk‐3FTx was found to affect the compound action potential (CAP) and nerve conduction velocity of isolated toad sciatic nerve. This is the first report of a non‐conventional 3FTx from Naja kaouthia venom that reduces CAP for its neurotoxic effect. Further studies can be carried out to understand the mechanism of action and to explore its potential therapeutic application.